Biodiversidad y colonización liquénica de algunos monumentos en la ciudad de Salamanca (España). - Marcos, B. (Botanica Complutensis, 2001)
MARCOS LASO, B. 2001. Biodiversity and lichenic growth on some monuments in Salamanca city. Bot. Complutensis 25: 93-102. The lichens biodiversity of two monuments the Roman Bridge and the Cathedral of Salamanca has been studied, the medioambiental influence on the growth of lichens in this urbans monuments has been partly analysed. A catalogue of 52 species growth on principal substrate sandstone of Villamayor, tile, granite, schist and cement to give. Lecania baeomma (Nyl.) P. James & Laundon and the lichenicolous fungi Lecidea associata Th. Fr. are new to Spain, 24 are new and 14 second to Salamanca.
Keywords: Biodiversity; lichens; saxicolous; memorials; chorology; Salamanca; Spain